ESTIMATIVA DA VIABILIDADE DAS SEMENTES DE AVEIA PRETA POR MEIO DAS CARACTERÍSTICAS DO EXSUDATO - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
Scientific research in the field of Seed Technology is based on techniques that aim to reduce costs and time, standardize, improve and establish methods of analysis, to obtain results that characterize seed quality. In this research the viability of black oat seeds (Avena strigosa S.) was evaluated through the exudate characteristics, using the individual and mass methods. The objective of this study was to verify the hydration time (30, 60, 90 and 120 minutes) and the type of preparation (whole or cut seed) that make it possible to estimate the viability of black oat seeds by means of pH determinations, electrical conductivity and color variation of the exudate during the hydration of the seeds; water content, germination and seedling emergence were evaluated. The experimental design was the completely randomized, in a 4 × 2 factorial design (water hydration times and preparation types), with four replications; the analysis of variance (ANOVA) was calculated and the means were compared by the Tukey test, at a 5% probability level. It is not possible to estimate the viability of black oat seeds through pH, color variation using phenolphthalein and the electrical conductivity of the exudate of these seeds during hydration.
Keywords: Avena strigosa; germinação da semente; períodos de hidratação da semente; Avena strigosa; seed germination; periods of hydration of the seed; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA